Does Contracting out Matter to Financial Condition? The Case of New York Local Governments. Issue 6 (2nd November 2021) - Park, Ji Hyung; Noh, Shihyun
Abstract: Little scholarly research has paid attention to the collective impact of contracting out on local financial condition. Contracting out can enhance a fiscal state by allowing local officials for more buying power with lower service costs as well as less long-term liabilities. Beyond prior research on the effect of contracting in a service, this research offers evidence that higher levels of contracting out spending improve local financial condition regarding budget solvency and long-run solvency. However, external suppliers can deteriorate financial condition. The findings show that the improvement of budget solvency does not materialize at a certain level of contracting out spending, but this is not the case for long-run solvency. The expectation of financial condition improvement may rely on the degree to which practitioners deliver public services through contracting out. Thus, local officials may want to decide levels of contracting out services strategically.